ORATORLÍQ ÓNERINIŃ TÚRLERI HÁM FORMALARÍ - Kossheterova, A.J. (SCIENCE and SOCIETY, 2025)
In the article presents the theoretical foundations and analysis of the emergence of oratory culture and its types.